Therapeutic Efficacy of Ultraviolet C Light on Fungal Keratitis—In Vitro and Ex Vivo Studies - Mark A. Bosman; Jennifer P. Craig; Simon Swift; Simon J. Dean; Sanjay Marasini (Antibiotics)
Objective: Fungal corneal infections are challenging to treat due to delayed diagnostic procedures, bacterial co-infections, and limited antifungal efficacy. This study investigates the therapeutic potential of ultraviolet C (UVC) light alone and combined with antifungal drugs. Methods: A subsurface infection model was developed in semi-solid agar droplets, with Candida albicans cells or Aspergillus brasiliensis spores inoculated into 0.75% w/v yeast peptone dextrose (YPD) agar in a 96-well microplate (5 µL per well). Two treatment groups were tested: (1) UVC exposure (265 nm, 1.93 mW/cm2) for durations of 0 s, 5 s, 10 s, 15 s, 30 s, 60 s, or 120 s, and (2) UVC combined with antifungal drugs (Amphotericin B and Natamycin) at their minimum inhibitory concentrations (MICs), determined in YPD broth. After treatment, agar droplets were homogenized, diluted, and plated for microbial enumeration. The most effective UVC doses were further tested in an ex vivo C. albicans porcine keratitis model, where the corneal epithelium was debrided, infected with C. albicans, and exposed to UVC. Corneas were then homogenized and plated to evaluate treatment efficacy. Results: UVC exposure of ≥15 s inhibited C. albicans, and ≥10 s inhibited A. brasiliensis (all p < 0.05). The broth MICs were 0.1875 µg/mL for Amphotericin B against C. albicans, 6.25 µg/mL against A. brasiliensis, and 0.78125 µg/mL for Natamycin against C. albicans, 7.8125 µg/mL against A. brasiliensis. The broth MIC did not eradicate fungi in the subsurface model. Combined treatments enhanced inhibition (all p < 0.05), with 30 s UVC + amphotericin B for C. albicans (p = 0.0218) and 30 s UVC + natamycin for A. brasiliensis (p = 0.0017). Ex vivo, 15 s and 30 s UVC inhibited growth (p = 0.0476), but no differences were seen between groups (all p > 0.05). Conclusion: UVC demonstrated strong antifungal efficacy, with supplementary benefits from combining UVC with low doses of antifungal drugs.